Preclinical Positron Emission Tomographic Imaging of Acute Hyperoxia Therapy of Chronic Hypoxia during Pregnancy - Alexander Zheleznyak; Joel R. Garbow; Michal Neeman; Suzanne E. Lapi (Molecular Imaging)
The goal of this work was to study the efficacy of the positron emission tomography (PET) tracers 2-deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG) and 64 Cu-diacetyl-bis(N4-methylthiosemicarbazone) ([ 64 Cu]ATSM) and in monitoring placental and fetal functional response to acute hyperoxia in late-term pregnant mice subjected to experimentally induced chronic hypoxia. E15 mice were maintained at 12% inspired oxygen for 72 hours and then imaged during oxygen inhalation with either [ 18 F]FDG to monitor nutrient transport or 64 Cu-ATSM to establish the presence of hypoxia. Computed tomography (CT) with contrast allowed clear visualization of both placentas and fetuses. The average ratio of fetal to placental [ 18 F]FDG uptake was 0.45 ± 0.1 for the hypoxic animals and 0.55 ± 0.1 for the normoxic animals, demonstrating a significant decrease ( p = .0002) in placental function in dams exposed to chronic hypoxic conditions. Hypoxic placentas and fetuses retained more 64 Cu-ATSM compared to normoxic placentas and fetuses. Herein we report first-in-mouse PET imaging of fetuses employing both tracers [ 18 F]FDG (metabolism) and 64 Cu-ATSM (hypoxia). [ 18 F]FDG PET/CT imaging allowed clear visualization of placental-fetal structures and supported quantification of tracer uptake, making this a sensitive tool for monitoring placental function in preclinical rodent models. These measurements illustrate the potentially irreversible damage generated by chronic exposure to hypoxia, which cannot be corrected by acute exposure to hyperoxia.